Investigation of engine failures of quarry dump trucks - L.A.; A.O.; S.S.; S.V.; N.V. (Технічна інженерія, 2023)
This work deals with malfunctions of career cars. Thanks to the conducted research, it was found that the cost of repair increases with the increase in the service life of the dump truck, and it is determined by the cost of repairs at the beginning of the operation of the dump truck, as well as the rate of increase in maintenance and repair costs as the mileage of the vehicle increases.